Transformational Leadership in Private Universities in Dki Jakarta - Sugiana, I Wayan; Talib, Azlizan; Yusoff @ Abdul Rahman, Mohd Nazaruddin (EPRA IJRD, 2021)
The study of transformational leadership has received a lot of attention among academics in many fields of study including higher education. At the higher education level, transformational leadership can be cited as the key to success. This study aims to describe the perceptions of leaders and educational staff about transformational leadership at the universities where they work. Data were collected from the leader and educational staff of leading private universities in DKI Jakarta which are included in clusters 1-3 based on the results of the higher education clustering of the Ministry of Education and Culture. The data obtained from the questionnaire were analyzed using descriptive statistics. The results showed that leaders of leading private universities in DKI Jakarta have implemented transformational leadership which is characterized by charisma, high social abilities, vision for the future, transactional abilities when needed, good delegation of authority, and ability to become capable executors